Effects of Nalbuphine with Morphine on Mean Systolic and Mean Diastolic Blood Pressures after Laryngoscopic Tracheal Intubation in Elective Coronary Artery Bypass Grafting - Mehreen Khan, Ravi Kumar, Udesh Kumar, Vijai Kumar, Hira Shujaat, Hiranand (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The raise in mean blood pressure and heart rate associated with intubation and laryngoscopy is harmful for patients of ischemic heart disease, hypertension, raised intracranial and intraocular pressure. To counter this problem nalbuphine began to be used. Nalbuphine is an opioidagonist antagonist which acts on ê receptor as agonist and on μ receptors as antagonist. We chose to study its haemodynamic response to orotracheal intubation. Aim: To compare the mean systolic and diastolic blood pressure with nalbuphine with morphine after laryngoscopic tracheal intubation in elective coronary artery bypass grafting. Methods: The study was a randomized controlled trial. 100 patients fulfilling selection criteria were included in the study from Operation theatre of Department of Cardiac Surgery, National Institute of Cardiovascular Diseases, Karachi. Patients were randomly divided in two equal groups by using lottery method. In group A, morphine was administered and in group B, Nalbuphine were administered during induction of general anaesthesia. History was taken from patients. Demographic information like age, gender and co-morbid. Patients were followed for results of the study. All information of was noted and entered in the Proforma. Results: One hundred patients fulfilling selection criteria were included in the study. In group A, morphine was administered and in group B, Nalbuphine were administered during induction of general anaesthesia. Comparison of SBP and DBP has been done between both of the study groups mean and SD of SBP in morphine group was 113.16 and 9.15(p-value=0.007), in nalbuphine group 120.90 and 11.46(p-value=0.03), respectively. Conclusion: It had been considered that morphine offers better analgesic conditions, but it also cause hemodynamic instability. nalbuphine can help in preventing anaesthesia complications, and cause less hemodynamic instability which results in less requirement of maintenance drugs for attenuation. This study to confirmed that nalbuphine can help in less fluctuation in hemodynamic conditions of the patients as compared to morphine. Keywords: Coronary artery bypass grafting, systolic blood pressure, diastolic blood pressure, nalbuphine, morphine